1.25 Å resolution structure of an RNA 20‐mer that binds to the TREX2 complex. Issue 10 (1st October 2015) - Valkov, Eugene; Stewart, Murray
<x xml:space="preserve">Abstract</x> The 1.25 Å resolution H32:R crystal structure of a 20 nt ribonucleotide that binds to the TREX‐2 complex with high affinity shows a double‐stranded RNA duplex arranged along a crystallographic 31 axis in which the antiparallel chains overlap by 18 nucleotides and are related by a crystallographic twofold axis. The duplex shows C–A, U–U and C–C noncanonical base pairings together with canonical Watson–Crick A–U and G–C pairs and a G–U wobble.